2016
DOI: 10.1074/jbc.m116.730135
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoside Triphosphate Phosphohydrolase I (NPH I) Functions as a 5′ to 3′ Translocase in Transcription Termination of Vaccinia Early Genes

Abstract: Vaccinia virus early genes are transcribed immediately upon infection. Nucleoside triphosphate phosphohydrolase I (NPH I)is an essential component of the early gene transcription complex. NPH I hydrolyzes ATP to release transcripts during transcription termination. The ATPase activity of NPH I requires single-stranded (ss) DNA as a cofactor; however, the source of this cofactor within the transcription complex is not known. Based on available structures of transcription complexes it has been hypothesized that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…It has previously been demonstrated that both Rap94 and VTF/CE are involved in the recognition of the termination motif, which may pause the elongating polymerase (Christen et al, 2008;Luo et al, 1995;Tate and Gollnick, 2015). NPH-I may then cause transcript extrusion from the active site by a 5 0 to 3 0 translocase activity on the non-template strand (Hindman and Gollnick, 2016;Tate and Gollnick, 2011). Provided the observed location of the CEC near the putative RNA exit tunnel is relevant for a termination intermediate, CEC may be involved in the recognition of the termination signal.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been demonstrated that both Rap94 and VTF/CE are involved in the recognition of the termination motif, which may pause the elongating polymerase (Christen et al, 2008;Luo et al, 1995;Tate and Gollnick, 2015). NPH-I may then cause transcript extrusion from the active site by a 5 0 to 3 0 translocase activity on the non-template strand (Hindman and Gollnick, 2016;Tate and Gollnick, 2011). Provided the observed location of the CEC near the putative RNA exit tunnel is relevant for a termination intermediate, CEC may be involved in the recognition of the termination signal.…”
Section: Discussionmentioning
confidence: 99%
“…Although Rap94 and other transcription factors must be displaced from the vRNAP surface to form the CCC, they can remain flexibly associated with the polymerase in the infected cell. After 5 0 cap synthesis, transcription elongation can proceed to the end of the gene, where termination is mediated by NPH-I and VTF (CE) (Christen et al, 1999;Hindman and Gollnick, 2016). In the future, structural insights into initiation and termination should reveal how the virus-specific factors Rap94, VETF, and NPH-I mediate these phases of the transcription cycle.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism and structural basis of termination by these factors remains opaque. Termination of early VACV genes is not reliant on A18, but by D11 (aka NPH-I) ( 83 , 84 ) or I8 (NPH-II) ( 85 87 ), which terminate transcription immediately following pyrimidine-rich sequences, both in the absence and presence of the upstream UUUUUNU motif ( 23 ).…”
Section: Discussionmentioning
confidence: 99%